Quality of life in COVID survivors and post COVID manifestations in a tertiary care hospital, Nalanda, Bihar - Shekhar, Shreya; Kishor, Aman; Zaman, Zaki Anwar (International Journal of Basic & Clinical Pharmacology, 2023)
Background: COVID-19 pandemic had affected majority of the population across the world. Majority of the cases still complaining of post COVID symptoms. This study was undertaken to study the various pattern of post COVID-19 manifestations in this region in a group of patients attending hospital. Methods: An observational study was undertaken in a group of 120 patients attending a tertiary care hospital. The patients were subjected for a detailed history and thorough physical examination and the details were entered in to a proforma. The data thus obtained was compiled and analysed. Results: This study had shown than majority of cases were aged more than 50 years and most of them were females. The common post COVID-19 manifestations included joint pain, continued loss of taste and smell, dyspnoea, Anxiety/ depression and sleep disturbances in this study. Conclusions: This study had observed continued symptoms from the episode of disease varying from mild to severe manifestations. This study urges for a comprehensive rehabilitation program for all COVID-19 patients.